2022
DOI: 10.46325/jnpra.v1i03.27
|View full text |Cite
|
Sign up to set email alerts
|

Antihemolytic and antioxidant activities of aerial parts extracts of Zygophyllum album L. and Globularia alypum L. from Algeria

Khaoula OUFFAI,
Rachid AZZI,
Fayza ABBOOU
et al.

Abstract: The main intrest of this study was to evaluate the antihemolytic and the antioxidant activities of the aqueous extracts of Globularia alypum and Zygophyllum album prepared by three different methods:  decoction, infusion and maceration. Phytochemical tests, total phenolic, flavonoid and tannins contents of the different aqueous extracts were determined. DPPH radical scavenging assay and Ferric Reducing Antioxidant Power (FRAP) were employed for the evaluation of the antioxidant activity. Whereas, the antihemol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Two methods were used to quantify this activity: the ferric reducing antioxidant power (FRAP) and the DPPH radical scavenging assay. The data obtained indicated that G. alypum exhibited significant concentrations of scavenging activity: IC50 223.04 ± 0.73 to 85.37 ± 1.48 µg/mL and EC50 0.31 ± 0.01 to 0.68 ± 0.19 mg/mL [19]. The variety seen in the antioxidant activities of G. alypum might likely be explained by the experimental setup, the methods employed, and the utilization of plants from various geographical regions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Two methods were used to quantify this activity: the ferric reducing antioxidant power (FRAP) and the DPPH radical scavenging assay. The data obtained indicated that G. alypum exhibited significant concentrations of scavenging activity: IC50 223.04 ± 0.73 to 85.37 ± 1.48 µg/mL and EC50 0.31 ± 0.01 to 0.68 ± 0.19 mg/mL [19]. The variety seen in the antioxidant activities of G. alypum might likely be explained by the experimental setup, the methods employed, and the utilization of plants from various geographical regions.…”
Section: Discussionmentioning
confidence: 94%
“…Nowadays, many researchers around the world are working on plant extracts to develop new antimicrobial agents with enhanced safety and efficiency [15][16][17][18][19]. The prime objective of ethnopharmacology is to identify plants for medicinal importance with minimal side effects.…”
Section: Discussionmentioning
confidence: 99%